Factors Affecting Fear of Childbirth Among Urban Women in India: A Qualitative Study. (May 2022) - Sharma, Baby; Jungari, Suresh; Lawange, Ajinkya
There is increasing evidence shows that fear of childbirth (FOC) may have short- and long-term adverse effects on mothers and babies if left untreated. The childbirth process is an experience with many dimensions, multifaceted, and unique for each woman, still strongly influenced by the social-cultural context in which women belongs. To identify and explore the factors contributing to the fear of childbirth among recently delivered women of Pune city, India. The study used a qualitative study approach. A total of 15 in-depth interviews were conducted with women who have recently given birth in maternity hospitals. Interviews were conducted using an interview guide (open ended-questionnaire). Interviews were audio-recorded. The participants were called into a separate room for the interview; full privacy was given to the interviewees, thus making a safe and reliable environment. All collected interviews were transcribed and analyzed. Axial coding was used to develop codes into major themes contributing to FOC were derived. Seven major themes emerged from the analysis of the transcribed interviews. The seven major themes are fear related to the child, fear of parenthood, fear due to mode of delivery, negative pregnancy/delivery experience, psychological aspects attributed to fear of pregnancy, fear of pain, and social background. FOC occurs in most of pregnant women irrespective of parity. The determinants of FOC are influenced by women context; thus, variation in factors of FOC is observed. The FOC related factors show the complex interconnection between them, and it may vary from woman to woman and settings to settings concerning women context.